Targeting epigenetics: A novel promise for Alzheimer’s disease treatment - Jeremic, Danko; Jiménez-Díaz, Lydia; Navarro-López, Juan D. (Ageing research reviews, 2023)
So far, the search for a cure for Alzheimer Disease (AD) has been unsuccessful. The only approved drugs attenuate some symptoms, but do not halt the progress of this disease, which affects 50 million people worldwide and will increase its incidence in the coming decades. Such scenario demands new therapeutic approaches to fight against this devastating dementia. In recent years, multi-omics research and the analysis of differential epigenetic marks in AD subjects have contributed to our understanding of AD; however, the impact of epigenetic research is yet to be seen. This review integrates the most recent data on pathological processes and epigenetic changes relevant for aging and AD, as well as current therapies targeting epigenetic machinery in clinical trials. Evidence shows that epigenetic modifications play a key role in gene expression, which could provide multi-target preventative and therapeutic approaches in AD. Both novel and repurposed drugs are employed in AD clinical trials due to their epigenetic effects, as well as increasing number of natural compounds. Given the reversible nature of epigenetic modifications and the complexity of gene-environment interactions, the combination of epigenetic-based therapies with environmental strategies and drugs with multiple targets might be needed to properly help AD patients. •Epigenetic studies provided numerous data on the role of gene expression changes in AD.•Studies tend to be neuron-centric focused on DNA methylation, histone modification and non-coding RNAs.•Epigenetic should be incorporated in molecular etiology of AD at different levels of biological complexity•Preventative strategies against AD epigenetic factors ought to integrate with future multi-target therapies.